Effects of preinduction and intraoperative warming during major laparotomy - Bock, Matthias; Müller, J.; Bach, Alfons; Böhrer, Hubert; Martin, Eike; Motsch, Johann (British journal of anaesthesia, 1998)
We have investigated the influence of active warming before and during operation on blood loss, transfusion requirements, duration of stay in the post-anaesthesia care unit (PACU) and perioperative costs in 40 patients undergoing major abdominal surgery. Patients were allocated randomly to one of two groups: in the study group (n = 20), patients were actively warmed using forced air for 30 min before induction of general anaesthesia and during anaesthesia. Passive protection against heat loss consisted of circulating water mattresses, blankets and fluid warming devices, and was used both in the active warming group and in the control group (n = 20). At the end of surgery the change in core temperature was significantly less in the group of actively warmed patients (0.5 (SD 0.8) degree C vs 1.5 (0.8) degree C; P < or = 0.01). Blood loss and transfusion requirements were less in the actively warmed patients, who had a shorter duration of stay in the PACU (94 (SD 42) min vs 217 (169) min; P < or = 0.01) and a 24% reduction in total anaesthetic costs.
Elektronische Reproduktion der Druck-Ausgabe 13. Dezember 2017
Gesehen am 14.11.2023